Pattern and problems of alcohol use in Gampaha District. - Pathmeswaran, A (My University, 1997)
The study was undertaken to describe the alcohol consumption pattern and people's attitude towards alcohol, and to determine the extent of some health and socio-economic problems related to alcohol consumption in the gampaha district and to assess the burden of problems related to alcohol consumption on government hospitals and the police department.The findings suggest that if state interventions aimed at reducing alcohol consumption are to be effective existing laws should be enforced more effectively to reduce the availability of Kasippu.Educational programmes should be implemented to educate the drinkers about sensible/'safe' drinking.Special programmes should be targeted at young males from lower social calsses and the catholic church could play a role in reducing alcohol consumption in the catholic community.Counselling services should be made available at or near police stations to deal with marital problems reported to the police and to help people with problems related to alcohol consumption.